Edukasi Hukum dan Kesehatan : Sinergi Dosen Interdisipliner dalam Penguatan Literasi Hak Kesehatan - Muhammad Ahwan; Ucik Ernawati; Naylil Mawadda Rohma; Dyah Erlina Sulistyaningrum; Agus Suryanto; Suryadi Suryadi; Tri Rettagung Diana (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Public literacy regarding health rights remains low, especially in communities with limited access to legal and health-related information. This lack of understanding often leads to unfulfilled rights and unequal access to quality healthcare services, contributing to a cycle of inequity and poor health outcomes. In response to this issue, this community service program seeks to enhance public awareness of health rights through interdisciplinary education, combining the expertise of lecturers from legal and health sciences. The program’s activities include the development of educational modules designed to provide clear, accessible information about health rights, as well as interactive legal-health counseling sessions aimed at addressing specific concerns. Group discussions serve as a platform for individuals to engage with experts and peers, furthering their understanding of how to navigate healthcare systems and advocate for their rights. Additionally, printed materials are distributed to reinforce learning and serve as ongoing references for participants. The program targets communities with high needs for health literacy, focusing on empowering individuals to recognize their rights and take action to ensure their healthcare needs are met. It also encourages the collaboration of interdisciplinary academic staff, fostering a collective approach to community empowerment. By improving health literacy, the program aims to promote social equity and improve access to quality healthcare services for underserved populations. Through this initiative, participants are better equipped to make informed decisions regarding their health and advocate for fair treatment in the healthcare system.